Promoting Self-Regulated Learning of Vocational High School Students in Blended Environment - Estri Oktarena Ikrarini; Misiyah; Setyo Budi Sungkowo (Conscientia, 2020)
Improving the English writing skill of Vocational High School students seems to be a challenge for Indonesian teachers generally due to some factors, such as a limited time allotted for English classes. As for the limited time, students need to be encouraged in improving their English skills in various settings, including online classes. This article reflects how the blended learning model conducted during Penugasan Dosen di Sekolah program at SMK N 4 Yogyakarta brought some impacts on encouraging students to develop their self-regulated strategies during online sessions. It also outlines the strategies applied by the instructor and potential drawbacks in getting the students involved in a blended environment.